Hyponatraemia secondary to an inappropriately high release of antidiuretic hormone in cardiac tamponade. - Groves, P H (1990)
A spontaneous intrapericardial haemorrhage caused cardiac tamponade in a 29 year old paraplegic man who was being treated with warfarin. The associated persistent hyponatraemia, which was believed to be caused by an inappropriately high release of antidiuretic hormone, rapidly resolved after pericardiocentesis.